Research Mentorship A Developmental and Transformational Tool in Shaping and Sustaining African Women's Career Progression in Academia - Phaswana-Mafuya, Refilwe Nancy (UJ Press, 2023)
"The lessons drawn on in this book are clear: do not wait to reach some place or position in life where you feel like you are prepared to give back or pour into people; you are already prepared and positioned on some level!" Prof Glenda Gray, President and CEO of the South African Medical Research Council There are barely any research mentorship books despite many conversations on it within academia and the role it can potentially play in the development and retention of academics in the pipeline. Academic institutions, appear not to have any solid mentorship frameworks that can be used to guide academics in the provision of robust research mentorship programmes. This original book details how research mentorship helped the author, a black woman in a predominately male-dominated patriarchal environment and the 33 mentees whose expressions have been captured in the book, to reach the pinnacle of academia despite a severe shortage of African women who have ascended to leadership roles within academia. The book showcases the value of research mentorship in developing leadership and support to the next generation of academics as well as deduce lessons learnt that can help to carry the knowledge enterprise forward. Further, it illustrates how research mentorship aided African women researchers in navigating non-diverse environments, early career struggles, post-graduate studies, work-life challenges as well complexities of scientific productivity, professional visibility, scientific connectivity (networks and collaborations), and resource mobilization, among others. The book offers potential mentors and mentees context-specific guidelines for effective mentorship, and best practices to enable scale-up. It also demonstrates how mentorship can contribute towards inclusivity and diversity and thus aid in narrowing persistent disparities in research, science, and academia.